Respostas

2014-07-07T18:13:28-03:00
(x + 2)·(x-6) = 0
x² - 6x + 2x - 12 = 0
x² - 4x - 12 = 0
Δ = b² - 4.a.c
Δ = (-4)² -4.1.(-12)
Δ =16 + 48
Δ = 64
Δ = √64 = 8

x, = -b + √Δ / 2a
x, = 4 + 8 / 2.1
x, = 12 / 2
x, = 6

x,, = 4 - 8 / 2
x,, = -4 / 2
x,, = -2

Raízes:
S = {6, -2}
      
enho q copiar tudo?
tenho q copiar tudo?
Basicamente sim se for para um exercicio de colégio. E está bem resumido. kkkk
obrigada
nada*-*
2014-07-07T18:14:34-03:00
(x+2)(x-6)= x^{2} -6x+2x-12
 x^{2} +2x-18
Δ= (-2)^{2} ± \frac{ \sqrt{2+4.1.18} }{2}
X= \frac{-4+ \sqrt{36} }{2}
X= \frac{-4+6}{2} =1
X"= \frac{-4-6}{2} =-5 \\  \left \{ {{x=1} \atop {x"=-5}} \right.